THE ANALYSIS OF SPEECH ERRORS MADE BY THE MAIN ACTORS IN BAD BOYS I THE MOVIE AT EDUCATION FACULTY OF AL ASY ARIAH MANDAR UNIVERSITY 2014 - Muthmainnah Muthmainnah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2014)
This thesis discusses the errors of speech (speech errors) were included in the study psycholinguistics. In this thesis analyzed the object of speech is a mistake made by the two main characters in the film Bad Boys (the movie): Mike Lowrey, played by Will Smith and Marcus Burnett, played by Martin Lawrence. This analysis focused on speech that are common mistakes (common types of speech errors), the silent pause, filled pause, repeats, retraced false starts, false starts un-retraced, corrections, interjection. The objectives of this research are to find out the types of speech errors and the dominant types of speech errors are made by the main actors in Bad Boys I the movie. In doing this research, the writer used qualitative descriptive method. The population of this research is the original movie transcript. This research employs purposive sampling, the writer only took the main actors of this movie as samples. The most dominant types of speech errors made by Mike and Marcus is Silent Pause. From all the data analysis, the writer concludes that both of actors made many errors in their dialogues, although the actors act and speak based on the script but in the process of acting we realize that the “ideal delivery” is very difficult. The characters in movies sometimes make speech errors in their dialogues intentionally or unintentionally.